2022
DOI: 10.3389/fimmu.2022.1010345
|View full text |Cite
|
Sign up to set email alerts
|

Construction of prediction model of inflammation related genes in idiopathic pulmonary fibrosis and its correlation with immune microenvironment

Abstract: BackgroundThe role of inflammation in the formation of idiopathic pulmonary fibrosis (IPF) has gained a lot of attention recently. However, the involvement of genes related to inflammation and immune exchange environment status in the prognosis of IPF remains to be further clarified. The objective of this research is to establish a new model for the prediction of the overall survival (OS) rate of inflammation-related IPF.MethodsGene Expression Omnibus (GEO) was employed to obtain the three expression microarra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…Increasing evidence indicated that immune cells were associated with IPF (Dai et al, 2022; Moss et al, 2022; Yin et al, 2022). In addition, monocyte count had been found to be a prognostic biomarker for patients with IPF (Kreuter et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence indicated that immune cells were associated with IPF (Dai et al, 2022; Moss et al, 2022; Yin et al, 2022). In addition, monocyte count had been found to be a prognostic biomarker for patients with IPF (Kreuter et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, given the immune system is central to the maintenance of normal, physiological deposition of ECM [12] , immunology has been the hot research topic in the eld of IPF. Numerous research has revealed the difference in immune cell in ltration between IPF patients and healthy controls [13][14] and immune response involved in in ammation response and brosis process in IPF [12,15] . Although several studies have demonstrated the interaction between lactate metabolism and immune response; however, such studies have mainly focused on oncology, viral infection, and sepsis [16][17][18] , while the clear characterizations and mechanisms of the underlying lactate metabolism-immunity in IPF remain poorly understood.…”
Section: Introductionmentioning
confidence: 99%